PENGARUH ZAT PENGATUR TUMBUH TERHADAP PEMBENTUKAN DAN PERTUMBUHAN SERTA KANDUNGAN SINENSETIN DALAM KALUS PADA TANAMAN KUMIS KUCING (Orlhosiphon arislatus ) - SITTI FATIMAH SYAHID; HERNANI HERNANI (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
Effect of growth regulator on the formation, development and sinenselin content of the callus on Orthosiphon aristatusEffect of growth regulators on the formation, development and sinenselin Content of the callus on kidney plant ( Orthosiphon arislatus ) was studied al the laboratory of the Research Insitute for Spices and Medicinal Crops ( RISMC ) Bogor from March lo October 2000. Material ( explains ) lor Ihe study was the sterile leaves available in the culture. Basic medium used was Murasige and Skoog ( MS ). The study was conducted in two step. In (he irst step Ihe explains were cultured un MS medium applied with 2 4-1) at the concentration of 0.1; 0.3; 0.5 and 0.7 mg/1. In the second step, the cxplants were cultured on MS medium containing 0 I mg/1 2 4-D (best concentration in Ihe lirsl study) enriched with BA at the concentration of 0.5; 1.0, and 1.5 mg/1. The experiment was designed as a completely randomized in three replicates Eaeh replicate contained live bottles. Parameters used for evaluating Ihe effect of treatment were ihe lime of initiations, growth rate, structure and colour of the calli and sinenselin content which was analyzed with IIPI.C. Results showed thai from the irst experiment, 2.4-1) of 0.1 mg/1 produced Ihe highest rate of calli formation(0.49 g/5 weeks), from Ihe second ex¬periment, il was revealed that Ihe best treatment was 0.5 mg/1 BA Combined with 0.1 mg/1 2 4-1) produced 6.59 g calli/5 weeks, but was not signiicantly different front the calli cultured on the medium containing 1.0 nig/l BA combine with 0.1 mg/1 2.4- D. Result of sinenselin analysis showed thai MS medium containing BA 1 .0 mg/+ 0.1 mg/1 2.4- I) produced (I 24% sinenselin. higher than those of other treatment.